In Silico Study of the Potential Anti-Cancer Secondary Metabolites of Beligo Plants (Benincasa Hispida) as Tyrosine Kinase Enzyme Inhibitors - Dewi, Tanaya Jati Dharma; Lutfi, Indra Dwi; Wafi, Abdul; Soranda, Rizky Febrian (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2025)
Cancer is a disease that contributes to the highest death rate in the world. One of the therapies to treat cancer is Epidermal Growth Factor Receptor-Tyrosine Kinase Inhibitors (EGFR-TKIs) therapy, one of which is erlotinib, whose mechanism of action is to inhibit the phosphorylation and activity of tyrosine kinase by competing for binding to EGFR ATP. Secondary metabolite compounds in Beligo ( Benincasa hispida ) are known to have the ability to inhibit carcinogenic activity and prevent malignant cell metastasis. This study aims to predict the physicochemical activity, toxicity and anticancer activity of beligo secondary metabolite compounds against tyrosine kinase receptors with the code 1M17. Prediction of physicochemical properties was carried out using the SwissADME Toxicity classes were carried out using the pkCSM Online Tool and ProTox Online Tool applications. The results of the LD 50 value and toxicity class classification were classified according to GHS. Prediction of binding affinity using the Molegro Virtual Docker application. The research results show that the secondary metabolite compounds hispidulin, catechin, naringenin, and quercetin in beligo have physicochemical properties that fulfill Lipinski's five laws. The predicted toxicity class of this compound is in the class 4-5 range and meets the parameters of Ames toxicity and hepatoxicity.  The secondary metabolite compounds hispidulin, catechin, naringenin, and quercetin in beligo are predicted to have potential as tyrosine kinase inhibitors and have Rerank score values ​​respectively: -79,424, -77,663, - 80,153, and -84,423. This compound also has steric bonds and hydrogen bonds that are similar to erlotinib from the same amino acid.